Мемуары: мемуары / Э. Г. Герштейн - Герштейн Эмма Григорьевна (ИНАпресс, 1998)
Экземпляры: аб. (2001) / Инвентарный номер: 43432 / Цена: / Сис.шифр: 83.3(2Рос=Рус)6 / Авт.знак: Г 42 / ГРНТИ: 17.07 / ББК: 83.3(2Рос=Рус)6-8Герштейн